The economic geography of development banking for sustainable development - Shah, A (2019)
The topic of this thesis is the economic geography of development banking for sustainable development. There are two primary research questions pursued in the thesis. The first question is: are development banks effective financial institutions for sustainable development? The second question is: what impact does the spatial scale of a development bank have on its possible effectiveness for sustainable development? The conceptual framework is comprised of four inter-related concepts: theoretical space, contextual place, structure of channels and organizational flow. The research was undertaken with a mixed-methods approach. The research was pursued in a case study format, and consisted of a close examination of four development banks: the Asian Development Bank (ADB), the Uganda Development Bank Limited (UDBL), the New York Green Bank (NYGB) and the Connecticut Green Bank (CGB). The four development banks were chosen for a combination of reasons, including spatial scale, varied geographical contexts and accessibility. The thesis resulted in three sets of conclusions, focusing on the effectiveness of development banks, the relevance of spatial scales for development banks and the conceptual foundations and methodology of assessing development banks. First, with regards to effectiveness, I conclude that development banks satisfice their mandates regarding the promotion of development, with the external context of a development bank significantly impacting its effectiveness. Second, with regards to spatial scales, I conclude that the optimal spatial scale of a development bank is related to the scale of the intervention that the development bank intends to make and what may be needed for development outcomes to be reached. Third, with regards to conceptual foundations and methodology, I conclude that the conceptual foundations upon which development banks exist are partially supported by empirical observation, and that analyzing the effectiveness of a complex institution can be meaningfully simplified by limiting the analysis to a single factor of analysis. The conclusions of the research could have a significant impact on the collective understanding of the role development banks can play in global efforts towards sustainable development.